1984
DOI: 10.3102/00028312021001025
|View full text |Cite
|
Sign up to set email alerts
|

The Visualization of Rotation in Diagrams of Three-Dimensional Structures

Abstract: Two experiments were carried out to investigate how remedial instruction may be given to students who have difficulties in visualizing the diagrammatic representation of a three-dimensional structure after the structure has been rotated. Experiment I demonstrated that two methods using models and diagrams were significantly better than a method that used only diagrams. The use of shadows with the models was significantly better than the use of models on their own. Experiment II investigated different ways of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
17
0
1

Year Published

1984
1984
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(18 citation statements)
references
References 11 publications
0
17
0
1
Order By: Relevance
“…1 represented the structures in the upper diagrams after rotation about the three Cartesian axes respectively. These results have alarming implications, and it is obviously necessary to devote considerable effort in devising special teaching methods which can be used, either in a remedial way for students in sixth-forms and universities, or as an integral part of lower levels of the curriculum.Two different methods of teaching students to visualise rotations have recently been described by Seddon, Eniaiyeju & Jusoh (1984), who reported successful results with Nigerian students at college and university level. In one method, students were required to observe real models actually rotating, and simultaneously to 189…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…1 represented the structures in the upper diagrams after rotation about the three Cartesian axes respectively. These results have alarming implications, and it is obviously necessary to devote considerable effort in devising special teaching methods which can be used, either in a remedial way for students in sixth-forms and universities, or as an integral part of lower levels of the curriculum.Two different methods of teaching students to visualise rotations have recently been described by Seddon, Eniaiyeju & Jusoh (1984), who reported successful results with Nigerian students at college and university level. In one method, students were required to observe real models actually rotating, and simultaneously to 189…”
mentioning
confidence: 97%
“…Two different methods of teaching students to visualise rotations have recently been described by Seddon, Eniaiyeju & Jusoh (1984), who reported successful results with Nigerian students at college and university level. In one method, students were required to observe real models actually rotating, and simultaneously to compare the changing outlines with those of the corresponding shadows of the same models throughout the rotation.…”
mentioning
confidence: 97%
“…While the technique based upon the models has been found to be effective with a variety of age groups (Seddon, Eniaiyeju andJusoh 1984, Jusoh 1979), it has also been found that the sequential presentation of the diagrams was not at all effective in teaching the visualization of rotations to 15-year old English students (Seddon, El Farra and Jusoh 1984). Perhaps the demands of understanding the diagrammatic sequences were too abstract for students at this level of cognitive development, whereas the models provided a more appropriate concrete form of representation.…”
Section: Rotation Aboutmentioning
confidence: 99%
“…Hence, in devising methods of instruction Seddon, Eniaiyeju and Jusoh (1984) have focused on teaching students exactly how the profiles should change for rotations about a particular axis. In one technique, students observe models of three-dimensional models rotating, and simultaneously relate each changing profile to the model's shadow projected by a light bulb placed in the student's line of vision to the model.…”
mentioning
confidence: 99%
“…Para isto é necessário que a representação seja dinâmica, podendo desse modo aprimorar a visualização tridimensional. SHUBBER, 1985;MOORE, 1986;TUCKEY et al, 1991).…”
Section: Introductionunclassified